Children's and parents' perceptions concerning surgical attire: a systematic review - Luciana Butini Oliveira; Carla Massignan; Isabel Cristina Quaresma Rêgo; Maria Marlene de Souza Pires; Bruce Dick; Michele Bolan; Graziela De Luca Canto
ABSTRACT Objective: To review the literature about children's and parent's perceptions on surgical attire. Data source: A systematic search was conducted in the databases EMBASE, Latin American and Caribbean Health Sciences (LILACS), PubMed, PsycINFO, Scopus and Web of Science. Grey literature was searched on Google Scholar, Open Grey and ProQuest Dissertations, and Theses Database. Data synthesis: A total of 2,567 papers were identified. After a two-phase selection, 15 studies were included in narrative synthesis. Children favored wearing white coats in five of the nine included studies (55.5% [95%CI 48.3-62.7]; p=1.00). With respect to parents' preferences, results of vote counting showed that in 11 of 15 included studies, they favored physicians wearing white coats (73.3% [95%CI 67.9-78.6]; p=0.11). Conclusions: Children and parents have preferred physicians to wear a white coat with a very low certainty of evidence.